SPORTS-RELATED ELBOW ULNAR COLLATERAL LIGAMENT INJURY IN THE 21ST CENTURY. Issue 4 (1st February 2017) - Zaremski, Jason; McClelland, JoAnna; Vincent, Heather; Vincent, Kevin; Herman, Daniel; Smith, Michael Seth; Prine, Bryan; Farmer, Kevin; Moser, Michael; Horodyski, MaryBeth
Abstract : Background: Elbow ulnar collateral ligament (UCL) injuries are common injuries in adolescent athletes, particularly overhead athletes. Surgical UCL incidence and outcomes are well-researched, but non-surgical UCL injury patterns and management in developing athletes are not clear. Objective: To determine patterns of UCL injuries among competitive athletes aged 11–22 years. We hypothesized that non-surgical UCL injuries occurred more frequently in younger athletes during the time frame of 2000–2016. Design: Descriptive epidemiological study. Setting: Academic, tertiary medical center. Patients (or Participants): Electronic medical records and key word searches were used to identify patients with UCL injuries sustained during competitive athletics (N=136). Interventions (or Assessment of Risk Factors): Age, time of injury by year, sport classification, sex. Main Outcome Measurements: UCL injuries and severity; injury management (surgical, non-surgical). Results: There were 53 surgical and 83 non-surgical UCL injuries. Non-surgical cases increased nine-fold from 2009–2016 compared to 2000–2008. Injury distribution was as follows: 60 sprains, 39 partial tears, 36 ruptures, 1 re-rupture. 92% of sprains did not undergo surgical intervention, whereas 51% of partial tears and 78% of ruptures underwent UCL-Reconstruction (UCL-R). There are increasing numbers of UCL injuries with increasing age; X 2 (4, 136)=14.209, p=0.007. Non-surgical UCL injuries occurred in highest frequency in the youngest athletes (100% of total injuries in 11–13 years; 71.4% of 14–16 years; 44.3% of 17–22 years). UCL injury volume was most commonly associated with the sports baseball (OR 1.55, p=0.32; 95% CI 0.69–3.51), softball (OR 0.76, P=0.76, 95% CI 0.22 to 2.68), American football (OR 0.50, p=0.48; 95% CI 0.10–2.59, and javelin (OR 6.69, p=0.07; 95% CI 0.72–61.62). Conclusions: Younger athletes are sustaining more frequent, less severe UCL injuries. Enforcement of appropriate rest, proper sport-related mechanics and diversifying sport participation are important to prevent a) UCL injury at a young age, and b) progression of a non-surgical injury to a potential UCL-R.